Psychic wholeness in the context of Anna Terruwe and Conrad Baars’ theory of repressive neuroses - Lipska, Anna (Studia Psychologica: Theoria et praxis, 2019)
In the 1970s, two Dutch psychiatrists, Anna Terruwe and Conrad Baars, developed an innovative theory and therapy of repressive neuroses. Their theory was founded on the philosophical anthropology of Saint Thomas Aquinas. This approach to neuroses stemmed from the observation that contemporary psychiatry and psychology lacked philosophical underpinnings and that sciences thus formed were unable to help people. The key concept in the theory of repressive neuroses is psychic wholeness—the unity of the senses, the intellect, and will under the natural guidance of the last two of these. Stressing the great importance of this wholeness of human sensory and intellectual faculties for mental health has its consequences in the approach to and treatment of repressive neuroses. Every neurotic disorder is a kind of disintegration (repression of emotions and lack of intellectual control); therefore, the therapeutic process is supposed to effect a reintegration of distinct human faculties. The article presents the concept of psychic wholeness in the context of the theory of repressive neuroses, with special focus on Aquinas’ anthropology as the philosophical basis for this theory. Bowen’s concept of differentiation of self is also discussed and its similarities to psychic wholeness are pointed out.